1997
DOI: 10.1063/1.118704
|View full text |Cite
|
Sign up to set email alerts
|

Unusual capacitance behavior of quantum well infrared photodetectors

Abstract: We report experimental and simulation results of capacitance of quantum well infrared photodetectors (QWIPs). We found that the QWIP capacitance displays unusual behavior as a function of voltage and frequency, deviating far from the constant geometric capacitance value. At high voltages, capacitance starts with a negative value at low frequencies, increases above zero with frequency, and eventually decays to the geometric capacitance value. The magnitude of negative capacitance exceeds the geometric capacitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 12 publications
0
37
0
5
Order By: Relevance
“…According to the relationships (9), (10), for a given value of the current I, the current noise power spectrum should therefore vary as 1/N and the responsivity should be independent of N. However, deviations of the behavior of the dynamic and static photoresponse [7][8][9][10][11] and of the noise power spectra [26,27] have been reported.…”
Section: Noise Model For a Continuous Distribution Of Generation-recomentioning
confidence: 97%
See 1 more Smart Citation
“…According to the relationships (9), (10), for a given value of the current I, the current noise power spectrum should therefore vary as 1/N and the responsivity should be independent of N. However, deviations of the behavior of the dynamic and static photoresponse [7][8][9][10][11] and of the noise power spectra [26,27] have been reported.…”
Section: Noise Model For a Continuous Distribution Of Generation-recomentioning
confidence: 97%
“…Despite the relatively simple structure of the QWIPs, the physical processes responsible for their operation is fairly complex [7][8][9][10][11][12][13]. It has been shown that the non-uniformity of the space charge regions over the quantum well periods may affect the QWIPs operation.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that the series resistance in this RC circuit is due to tunneling mechanisms (which dominate the dark current at lower temperatures), which in turn are structure-and bias-dependent. The capacitance is a barrier capacitance that can give rise to a quantummechanical separation of charge by the barriers and has been described by Ershov et al 14 The unusual capacitance behavior of QWTPs with frequency and bias has also been observed by Ershov et al 15 We have applied our RC circuit model to several QWEP structures and found that it describes their low-temperature I-V characteristics very well.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed in samples as different as crystalline and amorphous semiconductor devices, [1][2][3][4][5][6][7][8][9] organic compounds, [10][11][12][13][14] composite materials/nanomaterials, 9,15-22 electrochemical cells, [23][24][25] geological samples, 26 biological membranes, [27][28][29] and even moist surfaces. 30 Furthermore, it has been shown that NCs can originate at interfaces as well as in the bulk of the materials.…”
Section: Introductionmentioning
confidence: 99%